Internal fat prolapse from ischiorectal fossa masquerading as currarino syndrome - Md Mokarram Ali; Amit Kumar; Rashi Rashi; Amit Kumar Sinha; Bindey Kumar (Wolters Kluwer Medknow Publications, 2022)
Pelvic magnetic resonance imaging (MRI) is the latest addition to already existing tools for evaluation of anorectal malformation (ARM). It provides detailed information about pelvic floor musculature as well as position of rectal pouch. However, lack of knowledge about normal pelvic floor anatomy can lead to misinterpretation of pelvic MRI which can create confusion and change in approach for surgery. A 14-month-old male child with diagnosis of ARM was evaluated with pelvic MRI. There was finding of abnormal protrusion of fat through the ischiorectal fossa which was misinterpreted as Currarino syndrome which created confusion immediately before posterior sagittal anorectoplasty. Pelvic MRI is highly informative while evaluating a case of ARM. However, a detailed knowledge of pelvic floor anatomy is mandatory to avoid wrong interpretation and misdiagnosis.